Karakterisasi dan laju pembakaran biobriket campuran sampah organik dan bungkil jarak (Jatropha curcas L.) - Eddy Kurniawan; Wahyudi Budi Sediawan; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2012)
The potential of biomass municipal waste and jatropha cakes is abundant, but has not been utilized. These materials can be converted into biobriquette via pyrolisis, which can be used as alternative fuel. Tar and tapioca adhesive were applied for the binder.In this study, briquettes with the mass fraction of jatropha cakes of 0, 25, 50, 75 and 100% were used. Research was done by performing carbonization, screening (35 mesh), mixing raw materials (municipal waste, jatropha cakes, tapioca adhesive and tar adhesive) and pressing at 1 kg/cm². Briquettes were then analyzed for compressive strengh, heating value, the moisture content, volatile matter, ash and fixed carbon. The combustion of the briquette was undertaken to study the rate of combustion.Mathematical model showed that the rate of combustion of the briquette with composition of municipal waste and jatropha oil cakes (25% : 75%) with adhesive tar was faster. Briquettes with adhesive tar produce smoke when burned, while briquettes with tapioca adhesive is smoke-free. Therefore it is more preferable. The proposed mathematical model describes the rate of combustion of the briquette well. The kinetic parameter of the rate of combustion were also obtained.